On the Position of /s/ in Slovak Consonant Clusters: an Acoustic and Perceptual Analysis (e-Journal of Linguistics, 2023)
The paper presents the results of research aimed at the acoustic andperceptual analysis of onset and coda clusters from standard Slovak thatviolate the principle of sonority. The research is based on Engstrandand Ericsdotter’s (1999) claim that clusters violating sonority areperceptually advantageous over those that follow the sonority principle.The analysis was carried out on a sample of test nonsense words withthe initial combinations /sp, st, sk/ and final combinations /ps, ts, ks/.The data were produced and evaluated by native Slovak languagespeakers. The results of the research support the assumption about theperceptual advantage of clusters that are not in accordance withsonority.
Keywords: Slovak; consonant clusters; sonority violation; acoustic analysis; perception